2008
DOI: 10.1063/1.2993335
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of flatband voltage roll-off studied with Al2O3 film deposited on terraced oxide

Abstract: Surface passivation of GaN and GaN/AlGaN heterostructures by dielectric films and its application to insulated-gate heterostructure transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 6 publications
0
19
1
Order By: Relevance
“…This type of Vfb roll-off has been observed previously. (24)(25)(26)(27)(28) We see no discernable effect on Vfb rolloff from the RTUVO treatments used during this study, other than what can reasonably be attributed to the observed interface layer growth during DUDU processing. Thus, we conclude that RTUVO treatments have little effect on the nature of the HfO 2 /SiO 2 interface.…”
Section: Methodscontrasting
confidence: 60%
“…This type of Vfb roll-off has been observed previously. (24)(25)(26)(27)(28) We see no discernable effect on Vfb rolloff from the RTUVO treatments used during this study, other than what can reasonably be attributed to the observed interface layer growth during DUDU processing. Thus, we conclude that RTUVO treatments have little effect on the nature of the HfO 2 /SiO 2 interface.…”
Section: Methodscontrasting
confidence: 60%
“…Moreover, was found to be 0.4 V in this system 39 and in a similar configuration 24 corresponding to other reports in the literature. 62,63 After taking into account these components of Eq. (4), the intercepts of Fig.…”
Section: Electrical Resultsmentioning
confidence: 99%
“…Therefore, Capacitance-Voltage (C-V) measurements might increase the uncertainty in the estimation of V FB shift, which result in the errors of the dipole magnitude estimation. On the other hand, V FB roll-off effects can also be observed for low EOT region [369][370][371], the detail reason for such roll-off effects are not clear yet, including the charge effects, and the dipole strength changes. Such deficiencies mean that the announced dipole models are not well established and need further improvement.…”
Section: Work Function Tuning By Interfacial Dipole In High-k Gate Stmentioning
confidence: 88%